Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/ijg.0000000000001882
|View full text |Cite
|
Sign up to set email alerts
|

Hypotony-associated Complications After Deep Sclerectomy: Incidence, Risk Factors, and Long-term Outcomes

Abstract: Precis: Chronic hypotony is not uncommon following deep sclerectomy (DS), but only a minor proportion of patients develop hypotony-associated complications. Numerical hypotony does not affect the visual outcomes. This study identifies factors associated with hypotony.Purpose: To investigate the incidence and risk factors of hypotony and hypotony-associated complications after DS.Methods: Retrospective cohort study of 1765 eyes (1385 patients) undergoing DS with or without cataract extraction between 2001 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
1
16
1
5
Order By: Relevance
“…The incidence of bleb leak in our study was also comparable to studies evaluating glaucoma filtering procedures [1,31] . The rate of hypotony requiring bleb revision in our study was lower than other similar studies and those reporting complications of DS and trabeculectomy [1,33] . Bleb needling with anti-fibrotic agent when there were signs of bleb failure evidenced by increased bleb vascularity with progressive IOP elevation or bleb encapsulation in our current study were less common than that reported by Sangtam et al [1] and Kozobolis et al [6] , which were 50% and 20.7% respectively.…”
Section: Discussioncontrasting
confidence: 77%
“…The incidence of bleb leak in our study was also comparable to studies evaluating glaucoma filtering procedures [1,31] . The rate of hypotony requiring bleb revision in our study was lower than other similar studies and those reporting complications of DS and trabeculectomy [1,33] . Bleb needling with anti-fibrotic agent when there were signs of bleb failure evidenced by increased bleb vascularity with progressive IOP elevation or bleb encapsulation in our current study were less common than that reported by Sangtam et al [1] and Kozobolis et al [6] , which were 50% and 20.7% respectively.…”
Section: Discussioncontrasting
confidence: 77%
“…Although 13% of the eyes showed chronic hypotony, the occurrence of hypotony-related complications was much less common (estimated 5-year incidence of 5.6%). 27 Similarly, Saeedi analyzed this complication in 753 eyes that underwent TRAB and also found that a minor proportion of the 14.9% of the eyes with late low IOP hypotony (defined as IOP ≤ 5 mmHg at or after 3 months postoperatively and all eyes that had objective signs of hypotony (choroidal detachment, shallow AC, hypotony maculopathy) and all eyes that had revision surgery for low IOP, regardless of time after surgery) suffered hypotony-related complications or required surgical intervention (8% and 5% of the eyes respectively). 28 In the same way, 62.5% of the eyes in our study had statistical hypotony but it was not associated with complications or required further interventions in most of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, deep sclerectomy, a nonpenetrating glaucoma surgery wherein the inner wall of Schlemm's canal and juxtacanalicular trabecular meshwork are removed, previously had reported rates of choroidal effusion development ranging from 7.6 to 11% [16], falling within the lower range of rates reported in GDD and trabeculectomies. However, Rabiolo et al [19] recently reported even lower rates of effusion development (43/1765 eyes, 2.4%) in eyes undergoing deep sclerectomy between 2001 and 2020 in two UK centres [19]. Even with the addition of procedures to further lower IOP following deep sclerectomy, rates of choroidal effusions are still relatively small.…”
Section: Risk Factors For Choroidal Effusion Developmentmentioning
confidence: 99%